2020
DOI: 10.3389/fpsyg.2020.00792
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Wave Longitudinal Study of Moderated Mediation Between High-Performance Work Systems and Employee Job Satisfaction: The Role of Relational Coordination and Peer Justice Climate

Abstract: Existing literature lacks studies that examine the indirect effect of high-performance work systems (HPWSs) on employee job satisfaction through employee-employee relations. Moreover, less is known about the boundary conditions of this indirect effect. This study sought to longitudinally examine the mediating role of a specific form of employeeemployee relations-relational coordination-in the relationship between HPWS and job satisfaction. Data were collected in three waves from the employees of commercial ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 100 publications
(148 reference statements)
0
19
0
Order By: Relevance
“…García-Rodríguez et al [27] found that employees' perceptions of diversity management have a positive and significant direct effect on job satisfaction. Haider et al [28] findings provided the support for the direct relationship between high performance work systems and job satisfaction. Sanchez-Manzanares et al [10] examined 74 studies that have analyzed organizational factors that influence job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 90%
“…García-Rodríguez et al [27] found that employees' perceptions of diversity management have a positive and significant direct effect on job satisfaction. Haider et al [28] findings provided the support for the direct relationship between high performance work systems and job satisfaction. Sanchez-Manzanares et al [10] examined 74 studies that have analyzed organizational factors that influence job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 90%
“…This study has shown that students can take the same training contents in less faceto-face time without affecting their satisfaction, as long as there are adequate levels of coordination and communication. The scientific literature defends that, as more contingent factors demand a need for organizational action, the more important the application of relational coordination principles becomes [5,31,34,35]. Therefore, the application of relational coordination as an innovative organizational model for higher education could be transferable to other universities.…”
Section: Discussionmentioning
confidence: 99%
“…The RC model has been studied in sectors such as banking [35], airlines [34], health [4,31], and entrepreneurship [33], showing that a higher level of RC significantly increases the quality of the organization's results, regardless of the sector. Furthermore, RC has been applied to higher education.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship dimension focuses on shared goals, knowledge, and mutual respect among all profiles of an organization [3,[22][23][24][25]. The RC model has been applied in different sectors such as healthcare [22], banking [26], or airlines [21]. In addition, it has been studied in HE, showing that an increase in RC leads to an improvement in the results [3,23,24,[27][28][29].…”
Section: Rc and Improvement Of Resultsmentioning
confidence: 99%